Recent Advances in Particulate Adjuvants for Cancer Vaccination. Issue 5 (18th September 2019) - Song, Cui; Li, Feng; Wang, Shuang; Wang, Jianghua; Wei, Wei; Ma, Guanghui
Abstract: By activating/stimulating antigen‐presenting cells (APCs) and efficiently inducing humoral or cellular immune responses, particulate adjuvants have become one of the most ambitious and promising strategies in cancer vaccination. A large number of materials have been studied for their use as particulate adjuvants, including inorganic materials, polymeric materials, liposomes, emulsions, and exosomes. According to their unique physicochemical properties, these particulate adjuvants mainly work in three aspects: antigen delivery, APC activation, and antigen cross‐presentation, and they show great promise in various antitumor applications. This progress report highlights the recent advances in the study of particulate adjuvants, ranging from their materials, functions, and physicochemical properties to their applications in cancer vaccination. Abstract : Particulate adjuvants show great potential in cancer vaccination. This progress report reviews the components, functions as well as physicochemical properties of particulate adjuvants, and highlights the current applications of particulate adjuvants in the field of cancer treatment, including prophylactic vaccines, therapeutic vaccines, anti‐metastasis vaccines, anti‐recurrence vaccines, and combination therapy.